What is the Role of International Law in Global Health Governance on the Period of Covid-19 - Batakis, Dimitrios; Sidiropoulos, Symeon; Vozikis, Athanasios (HAPSc Policy Briefs Series, 2020)
Rapid globalisation challenges many of the traditional assumptions about International law, which is linked to domestic law, especially the ways in which it is formed and the methods of its implementation. This phenomenon led governments to be more focused on international collaboration to achieve national public health purposes and succeed some audit over the cross-border powers that influence their populations. This essay will analyse the position on what is the role of international law in global health governance. Another significant result of this essay is that Global Actors should create a global health cooperation in order to implement the international law effectively on the period of Covid-19.